: Comparison of Laryngeal mask airway versus Endotracheal intubation in general anaesthesia for endovascular neurosurgery: A Prospective, Randomized Controlled Trial.: Airway management in endovascular neurosurgery - Khurana, Deepa Kerketta; Krishna, Bhavya; Kumari, Santosh; Mehta, Khushboo; Jain, Mansi; Chaudhary, Sujata (Journal of the Portuguese Society of Anesthesiology, 2025)
Introduction- Endovascular treatment of intracerebral aneurysms/arteriovenous malformations requires the neuro-anaesthesiologist to control and manipulate the haemodynamic parameters with minimum fluctuations. The aim of this study was to compare the performance of endotracheal intubation versus Laryngeal Mask Airway (LMA) ProSeal with respect to hemodynamic stability and adverse respiratory events in such procedures. Material and Methods- Ninety patients, with a pre-procedure Hunt and Hess Scale ≤ 2 and Glasgow Coma Scale (GCS) ≥ 13, scheduled for digital subtraction angiography (DSA) guided coiling of intracerebral aneurysms/AV malformations were randomly divided into two demographically comparable groups, namely endotracheal intubation (Group T) and ProSeal LMA (Group L).Heart rate (HR), systolic and diastolic blood pressure (SBP, DBP), mean arterial pressure (MAP) and oxygen saturation (SpO2) were noted at baseline and compared at 1min, 3min, 5min and 10min after intubation and extubation. Respiratory adverse events if any, were recorded. Results- With baseline vitals being comparable, a significant difference was seen post intubation in the HR at 1 min (p- 0.0355) and 3min (p-0.0217), SBP at 1min (p-0.0164) and 3 min (p-0.0008) and MAP at 1min (p–0.0001), 3min (p-0.0024) and 5min (p- 0.0031) after intubation, with Group T showing higher values. Post extubation, the rise in HR and MAP was higher in Group T (p- 0.0110 and 0.0190 respectively). Respiratory adverse were higher in Group T. Discussion and Conclusions- ProSeal LMA is an effective alternative in endovascular neurosurgery, providing stable perioperative haemodynamics and fewer respiratory adverse events. In cases where long term ventilation might be anticipated endotracheal intubation may be chosen.